Sobre as operações matemáticas e o cálculo mental - Ananias, Eliane Farias (2010)
By carrying out a research work on the use of games in mathematical education under Piaget´s constructivist perspective, we realized that was from the XX Century which more relevant contributions appeared under teaching proposes that incorporated the use of pedagogical materials. The research work and studies of Piaget, Grando, Brenelli, Bittar and Freitas, Mendonça and Lellis, Piaget and Chomsky, Costa, Parra, Alves and Ramos based the research work in question. From this reality, the research aimed to investigate, to intervene and to analyze cognitive aspects on the construction and recall of mathematical concepts (addition, subtraction, multiplication and division) and the ability of mental calculus in the teaching and learning of Mathematics by using the Calendar and the Dominó game having the four operations as resources. The research work carried out is presented as a case study done in a public primary school in the city of Campina Grande Paraiba, with twenty five students between ten to eleven years old. The data collection was done in five moments by the classroom being the research environment. The data was analyzed by taking into account three categories which emerged from the five moments. Triangulation was the technique used in our analyses. As findings, the research work has initially shown that the students were not conscious that they were able to do mental calculus. The classroom environment itself showed to be good for knowledge construction, as the students showed interest and good during all the moments of the research. In this context, the Mental Calculus, within the developed activities with the use of the Calendar and the Dominó Game for the four operations, contributed for the students to be conducted gradually for constructed and recalled mathematical concepts within the Mathematical Operations. For seeking cognitive structures equilibration, the group work, which was not the focus of our research work, has shown to be important factor in the development of the students cognitive aspects. The research work also provoke the students teacher reflection on the use of Mental Calculus and of ludic activities in the classroom, mainly in the teaching concepts on Mathematical Operations, making her to realize improvement on the students learning process.